Efektivitas Pemasaran Digital Vs Pemasaran Tradisional pada Dealer Mobil Honda Jabodetabek - Aditya Ivan; Theresia Gunawan; Istiharini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the comparative effectiveness of digital marketing and traditional marketing strategies at Honda dealerships in the Jabodetabek area. With the rapid advancement of technology, the marketing landscape has shifted significantly, requiring businesses to adapt and optimize their strategies to remain competitive. Traditional marketing methods, such as exhibitions, print advertising, and telemarketing, have long been utilized to reach potential customers. However, the rise of digital marketing leveraging platforms like social media, websites, and online advertisements offers new opportunities for cost-effective, targeted, and measurable marketing strategies. This research employs a quantitative approach using a survey method, involving sales consultants selected based on their sales performance. The collected data were analyzed using descriptive statistics and crosstab analysis to examine the relationship between demographic factors and marketing effectiveness. The findings indicate that social media is the most effective digital marketing channel, while dealer and international exhibitions remain highly relevant in traditional marketing. Conversely, telemarketing and print advertising are perceived as less effective. The study concludes that integrating digital and traditional marketing is crucial to maximizing sales performance. It is recommended that sales consultants receive skill training in digital marketing tools, allowing them to leverage technology effectively while maintaining personal customer engagement through traditional methods.